Cultural Communication in The Modern Media Age: A Study on Cultural Identity Theory and Its Significance for Inter-Cultural Communication in Kingdom of Bahrain (The International Journal of Educational Sciences and Arts, 2025)
The research seeks to understand the role of cultural identity theory and its importance in enhancing intercultural communication in the Kingdom of Bahrain, as the problem of the study was represented in the lack of a deep understanding of the impact of cultural identity on communication processes in Bahrain and its repercussions on interactions between individuals and societies. This research belongs to descriptive research, and the questionnaire will be used as a tool to collect data from members of Bahraini society. The research aims to study cultural identity theory and measure its effectiveness between cultures in the Kingdom and interpret the theoretical context of the study in light of this theory, and thus extract results for the purpose of addressing and analyzing the problem and then generalizing these results that work to provide a framework of understanding that helps to overcome cultural gaps and build bridges of communication and understanding. In addition, it contributes to enhancing cultural integration and peaceful coexistence between different cultures in one society.
Keywords: Cultural communication; Modern Media; Cultural Identity Theory; Kingdom of Bahrain